Standardization of nitrogen application for potted Chrysanthemum morifolium cv. kikiobiory - Tanya Thakur (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2020)
The present investigation was carried out to standardize nitrogen application for standard potted Chrysanthemum morifolium cv. Kikiobiory at Department of Floriculture and Landscaping, PAU, Ludhiana during the year 2015-16. Six treatments of nitrogen viz. 0, 100, 200, 300, 400 and 500 mg/pot were applied twice in the last week of September and October. The results of the study revealed that nitrogen application had significant effect on all the vegetative and floral parameters. The largest flower size (17.69 cm) was obtained with the nitrogen application of 400 mg/pot which was at par with 500 mg/ pot (17.67 cm). Application of nitrogen at 500 mg/pot recorded the highest plant height (75.47 cm), number of leaves per plant 75 days after planting (30.92), number of root suckers per plant (11.47) and delayed flower bud appearance (93.78 days), color break stage (122.59 days) and also shown flower quality deterioration by reducing the flowering duration (5.84 days) as compared to the other treatments. Therefore, it was concluded that 300 mg of nitrogen per pot applied twice was the standard dose for quality flower pot production in Chrysanthemum morifolium cv. Kikiobiory.